Effect of porosity morphology and elements characteristics on mechanical property in T-joints during dual laser-beam bilateral synchronous welding of 2060/2099 Al-Li alloys. (August 2021) - Chen, Dan; Zhan, Xiaohong; Liu, Ting; Zhao, Yanqiu; Qi, Na; Sun, Lulu
Highlights: Low welding speed or high laser power was harmful to reduce porosity. Effects of porosity distributions on the mechanical properties were studied. Effects of different grain morphology on the formation of porosity were analyzed. Influence of elements characteristics on porosity formation were studied. Abstract: The 2 mm thick 2060-T8/2099-T83 Al-Li alloy T-joints were welded by dual laser-beam bilateral synchronous welding (DLBSW) with ER4047 filler wire. The metallurgical porosity defects under different welding parameters were investigated to study the influence of laser power and weld speed on the porosity distribution, formation mechanism and mechanical properties during DLBSW process. In order to explore the special effect of welding heat input on the difference of alloying elements content around porosity, a comparative analysis of elements content between the porosity boundary and matrix around porosity was studied. It was found that the weld porosity defects were increased significantly as the laser power increased. Besides, the heat affected zone (HAZ) and branches of dendritic crystals were the key positions of porosity nucleation and formation. The results of tensile test and SEM of failure surface demonstrated that porosity was one of the important factors leading to weld bead failure. In particular, the porosity in the bottom fusion zone and EQZ significantly weakened the performance of the T-joint.